A Study of Inheritance Distribution from the Perspective of the Compilation of Islamic Law (KHI) and Civil Law: A Case Study in Kwaron and Grogol Villages, Diwek District, Jombang Regency - M. Lathif Bashar; Khoirul Anwar (International Journal of Law and Society, 2025)
This study aims to examine and compare the practices of inheritance distribution in Kwaron and Grogol Villages, Diwek District, Jombang Regency, from the perspectives of the Compilation of Islamic Law (KHI) and Civil Law. This qualitative research adopts a case study approach, collecting data through in-depth interviews, field observations, and document studies. The findings indicate significant differences in inheritance distribution practices between the two villages, influenced by social, cultural, and legal interpretive factors. The study also finds that legal ambiguity and limited public understanding of inheritance law often lead to conflicts. Moreover, it reveals that mediation and conflict resolution through customary and religious approaches tend to be more effective than formal legal processes. The study recommends enhancing public awareness of inheritance law and developing more integrative conflict resolution mechanisms.